Pemanfaatan “SAKESI” Sari Kedelai Melancarkan Produksi ASI - Ningrum, Nyna Puspita; Nuraini, Indria; Hubaedah, Annah; Andarwulan, Setiana (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: WHO and UNICEF recommend that newborns receive exclusive breastfeeding for 6 months in early life until the age of two years. The low level of exclusive breastfeeding in the community is caused by various challenges such as the assumption that the supply of breast milk is insufficient and the lack of knowledge about natural methods to increase breast milk production. Community service is carried out in RW II, Siwalankerto, Surabaya. Method: Using a natural approach, educational workshops and direct training in preparing soy milk, aimed at mothers, pregnant women, and posyandu cadres. This program focuses on the use of soy-based products, especially "SAKESI" (Soy Milk), as a natural method to increase lactation. Pre- and post-intervention surveys were conducted to assess changes in knowledge and behavior regarding exclusive breastfeeding and the use of soy products. The study findings showed significant improvements in both knowledge and practical application of these methods, indicating the effectiveness of the program in promoting breastfeeding practices. Conclusion: The project highlights the potential of an affordable local resource such as soybeans to address public health challenges related to maternal and child nutrition and also the importance of ongoing community education and support to sustain these improvements.